Evaluating the Development of Pre-Service Primary School Teachers' Competences in the Context of a Student-Centred Science Visits Course - Katarina Susman; Matej Vošnjak; Jerneja Pavlin (MDPI AG, 2024)
The student-centred approach emphasises active learning, where students take responsibility for their own learning process, in which they are actively involved and integrate new information into their existing knowledge framework. Combining this approach with outdoor learning provides an even more effective teaching strategy. When combining these approaches, the individual needs and interests of the students must be taken into account. The research was conducted as part of The Science Visits Course among 30 prospective primary school teachers in their final years of study. The focus of the study was on the students' self-assessment of their competences in science education and on the implementation of a student-centred teaching process, including outdoor teaching. Data were collected using online questionnaires and a structured evaluation form to assess students' plans for a science visit. The research findings suggest that students find this type of work engaging and that it encourages their self-engagement, taking responsibility and working together in a group through sharing ideas and opinions. On the other hand, the student competences important for outdoor education have come to the fore to some extent, but there are still areas that can be improved, especially in the area of science content knowledge.